Tinjauan Prinsip-Prinsip Seni Rupa Pada Gambar Bentuk Flora Teknik Stippling Hasil Karya Siswa - Indra Novianda; Nelson Tarigan (Mahesa Research Center, 2021)
This study aims to determine the results of students' work in drawing shapes in class XI SMA Negeri 2 Percontohan Karang Baru based on the principles of fine arts. The object in this study is a picture of the flora using the stippling technique. The population of this study amounted to 32 works of shape drawings and samples in this study were 10 works of shape drawings. This study used a qualitative descriptive method to find out how the results of the image work of the XI grade students of SMA Negeri 2 Percontohan Karang Baru first, then describe the image under study and assessed based on the principles of fine arts. The results of this study indicate that the overall work produced is based on the principles of fine arts as a whole on the principles of composition obtaining a score of = 75.33 in the Good category (B). On the principle of proportion, it gets a value of = 81 in the Good category (B). On the light-dark principle, the score = 82.5 in the Good category (B). Then the last one is on the principle of the shadows getting a value of = 72.33 in the Good category (B). Based on the description above, the highest score lies in the light and dark principle, and the overall average value is = 77.58 in the Good category (B).